A systematic review of microorganisms as indicators of recreational water quality in natural and drinking water systems - José Luis Lugo; Elkyn Rafael Lugo; Mario de la Puente (IWA Publishing, 2021)
The purpose of this review was to highlight the most frequent biological indicators used to estimate the microbiological quality of drinking and recreational water. It was observed that the incorporation of other microbiological indicators should be considered to strengthen the decision-making process on water quality management and guarantee its safe consumption in recreational activities.